The Razor’s Blind Spot: An Analytical Critique of the Atheistic Parsimony Argument (APA) - Haq , Zia ul (Millah: Journal of Religious Studies, 2026)
When competing hypotheses show equal explanatory strength, philosophers and scientists often prefer the simpler proposition in the process of theory selection. However, contemporary atheistic arguments, especially the APA, misappropriate parsimony by excluding the God hypothesis from the explanatory system. Here, I evaluate the legitimacy of the APA through an analytical method grounded in Thagard’s coherence principles and Swinburne’s explanatory model to examine whether simplicity alone can serve as a criterion for theory selection. The results show that the APA does not satisfy established coherence criteria, improperly elevating simplicity over explanatory power. Finally, the study proposes a Cross-Domain Coherence (CDC) model that emphasizes multidimensional approaches to theory choice beyond ontological minimalism, offering a framework capable of explaining reality in its full complexity.